Effects of ifenprodil treatment on pain behaviour, inflammation, and nociceptive responses in the spinal cord of complete freund’s adjuvant-induced chronic polyarthritis rat - Noh, Ain’ Sabreena Mohd (2024)
Rheumatoid arthritis (RA) is a chronic inflammatory condition characterised by frequent reports of pain. Ifenprodil, a selective N-methyl-D-aspartate receptor-2B (NMDAR-2B) antagonist, has demonstrated a significant anti-nociceptive effect in chronic pain models. This study aimed to investigate the effect of Ifenprodil as a selective NMDAR-2B antagonist on pain behaviour, inflammation, and nociceptive responses in the spinal cord of CFA-induced polyarthritis, as well as its possible side effect on memory function. Arthritic rats received intrathecal treatment of either Ifenprodil (0.5 or 1.0 μg/μL) or Sodium Diclofenac (6 μg) (positive control) whereas arthritic (A) and non-arthritic (C) control groups were administered with 0.9% normal saline for 7 days (day-16 to -22 post-arthritic induction). Ankle joint diameter and circumference, pain behaviour assessments including von-Frey and hot-plate tests, mobility scoring, and memory test were conducted on day-0 (baseline), day-15 (pre-intervention) and day-23 (post-intervention). Histopathological examination was performed on the ipsilateral ankle joint while the lumbar region of the spinal cord (L4-L5) was collected for ELISA, immunohistochemistry and RT-qPCR analyses. The group receiving Ifenprodil (0.5 μg/μL) showed a non-significant trend of increased body weight with no change in total food intake, attenuation of thermal hyperalgesia, tactile allodynia and improved mobility and significant improvement in the morphology of the ipsilateral hind paws and ankle joints when compared to the arthritic rats receiving Ifenprodil at 1.0 μg/μL. Meanwhile, Ifenprodil has significantly decreased the level of NMDAR-2B, substance P, BDNF and TNF-α proteins with attenuation on the total and phosphorylated NMDAR-2B, BDNF, activated microglia (Iba-1) and P2X4 receptor (P2X4R) mRNA and proteins expression in the polyarthritis rats. Furthermore, pro-apoptotic caspase-3, caspase-8, PKB, and PI3Kcb markers were decreased with no change in the anti-apoptotic Bcl-2 level in the spinal cord compared to the arthritis control group. A significant improvement in the memory discriminative index observed in the polyarthritis rats, especially at the concentration of 0.5 µg/µL implies a beneficial influence of Ifenprodil on memory enhancement. Thus, Ifenprodil, particularly at 0.5 μg/μL demonstrated significant anti-nociceptive and anti-inflammatory effects comparable to those of Sodium Diclofenac. These results underscore the potential involvement of NMDAR-2B activation in the pathogenesis of chronic arthritic pain.